ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE, PROFITALBILITAS, DAN UKURAN PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN SUSTAINABILITY REPORT - Handre Diono; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2017)
This study examined the impact of corporate governance mechanism, including board size, independent board, board with female commissioners, as well as the size of the company profitabilas and disclosure level sustainability report. This study uses regression test tool by using SPSS software version 20. The population in this study are all companies listed in Indonesia Stock Exchange for the fiscal year ended December 31, 2013-2015, and disclose sustainability report in 2013-2015. The sampling technique was conducted by purposive sampling method, so that the study sample was 91 companies.The result of multiple regression test shows that the size of the board of commissioners, independent board composition, women board compositon and profitability have positive and significant influence to sustainbility report disclosure level. The test results on firm size shows that firm size has a negative and significant impact on sustainability report disclosure.